Depression and Suicide Message as Seen in Chester Bennington of Linkin Park’s Selected Lyrics From 2000 (Hybrid Theory) Until 2017 (one more light) - Febrina Fitri Waskita; Raflis Raflis (Jurnal Ilmiah Langue and Parole, 2019)
Linkin Park consists of six people, namely Chester Bennington as the vocalist, Mike Kenji Shinoda as a rapper (founder of Linkin Park), Brad Philip Delson as a guitarist, David Micheal "Phoenix" Farrel as a bass, Joseph Hanh as a disc jockey (DJ) and Rob Gregory Bourdon as a drummer. The writer only focus on Chester Bennington’s life, how his struggle in roller coaster life and accept himself cannot separate with his suffered on his past. Chester Bennington always interpreted him become part of his songs in Linkin Park’s lyrics. This thesis is entitled "Depression and suicide message as seen in Chester Bennington of Linkin Park’s Selected Lyrics from 2000 (Hybrid Theory) Until 2017 (One More Light)" seen from the perspective of psychological analysis, pragmatics analysis, lyrics of songs analysis. This research is limited on basic ideas that relate to the observation into three questions as follow: (1) what makes Chester Bennington left his message in lyrics of Linkin Park’s songs, 2) what the causes Chester Bennington depression and decides to commit to suicide, and (3) What song proves Chester Bennington was depressed and decided to commit suicide. The objectives of this research were (1) To explain the reason Chester Bennington of Linkin Park had written down his stories into lyrics of Linkin Park’s songs (2) To explain the causes that Chester Bennington depression and decides to commit suicide, and (3) to explain that the songs of Chester Bennington was depressed and decided to commit suicide. The theory used is from a some sourceres by Sigmund Freud about Chester Bennington’s mental health. For searching his message is using by George Yule’s theory. For the method of data analysis, the author uses qualitative research. For searching seven lyrics of songs analysis using Dallin’s theory. This research is qualitative research using the content analysis method. The findings of this research is a song lyric, lyrics give the audience deep understanding about the message contained in the song.